The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3233/wor-208018
|View full text |Cite
|
Sign up to set email alerts
|

Desktop lighting for comfortable use of a computer screen

Abstract: BACKGROUND: The contrast between a bright computer screen and a dark ambient environment may influence comfort of the users, especially on their eyes. OBJECTIVE: The objective of this research is to identify the optimal desktop lighting for the comfortable use of the computer screen in a dark environment. METHODS: An experiment was designed where seven illumination setups were introduced for the users to perform their leisure tasks on a computer screen. Fifteen healthy subjects participated in the experiments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
1
4
2
Order By: Relevance
“…To sum up, in a short reading time of about 20 minutes, the visit time and frequency changed, the number and time of xation decreased, the unknown saccade increased, and the reading speed slowed down. Compared with studies on longer visual tasks reported over recent years [12,15],this study further found that the eye movement parameters signi cantly changed over a short period. As in such a relatively short period of time, asthenopia may not rise so signi cantly to be detected by the subject; this proves the potential of eye-tracking technology for sensitive assessment of asthenopia.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…To sum up, in a short reading time of about 20 minutes, the visit time and frequency changed, the number and time of xation decreased, the unknown saccade increased, and the reading speed slowed down. Compared with studies on longer visual tasks reported over recent years [12,15],this study further found that the eye movement parameters signi cantly changed over a short period. As in such a relatively short period of time, asthenopia may not rise so signi cantly to be detected by the subject; this proves the potential of eye-tracking technology for sensitive assessment of asthenopia.…”
Section: Discussioncontrasting
confidence: 51%
“…In addition, when healthy people are driving, their eye movements, such as saccade speed, may signi cantly change with the emergence of mental or physical fatigue [10][11]. While a limited number of studies on the association of asthenopia and eye movement have been reported in recent years [12][13][14][15], the e cacy of eye movement for the objective assessment of asthenopia needs to be further examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The visit time and frequency changed, the number and time of fixation decreased, the unknown saccade increased, and the reading speed slowed down. Compared with studies on longer visual tasks reported over recent years [ 12 , 15 ], this study further found that the eye movement changes can happen over a very short period of reading (20 min). As in such a relatively short time, asthenopia may not arise so significantly as to be detected by the subject; this demonstrates the potential of eye-tracking technology for sensitive assessment of asthenopia.…”
Section: Discussioncontrasting
confidence: 40%
“…In addition, when healthy people are driving, their eye movements, such as saccade speed, may significantly change with the emergence of mental or physical fatigue [ 10 , 11 ]. While a limited number of studies on the association of asthenopia and eye movement have been reported in recent years [ 12 , 13 , 14 , 15 ], the efficacy of eye movement for objective assessment of asthenopia needs to be further examined.…”
Section: Introductionmentioning
confidence: 99%